Rhodococcus rhodochrous IEGM 1362 Immobilized in Macroporous PVA Cryogel as an Effective Biocatalyst for the Production of Bioactive (–)-Isopulegol Compounds - Maltseva, Polina Y.; Plotnitskaya, Natalia A.; Chudinova, Alexandra A.; Ilyina, Irina V.; Volcho, Konstantin P.; Salakhutdinov, Nariman F.; Ivshina, Irina B. (Pharmaceuticals (Basel, Switzerland), 2025)
Background: This study explored the biotransformation of (–)-isopulegol using immobilized cells of Rhodococcus rhodochrous IEGM 1362 to optimize the production of new bioactive compounds. Methods: An efficient biocatalyst based on R. rhodochrous IEGM 1362 cells immobilized in a macroporous polyvinyl alcohol (PVA) cryogel matrix was developed for the production of bioactive derivatives of (–)-isopulegol. The biological characteristics of the immobilized cells were investigated using scanning and transmission electron microscopy and energy-dispersive X-ray spectroscopy methods. Results: The use of the biocatalyst increased the overall yield of target products from 54% with free cells to 87% with immobilized cells in a single cycle. Major derivatives identified included (1R,2S,5R)-5-(hydroxymethyl)-2-(prop-1-en-2-yl)cyclohexanol and (1R,3R,4S)-3-hydroxy-4-(prop-1-en-2-yl)cyclohexanecarboxylic acid, both exhibiting potential pharmacological activity. The biocatalyst retained functional activity toward monoterpenoid over 13 exploitation cycles, meeting industrial biotechnology requirements. Immobilized cells were characterized by the absence of endogenous reserve inclusions (in particular lipids) and a high intracellular iron content. Conclusions: The developed immobilized biocatalyst is promising for scaling up the production of biologically active compounds.